2003
DOI: 10.1046/j.1440-1843.2003.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

SARS: clinical virology and pathogenesis

Abstract: SARS: clinical virology and pathogenesis JOHN NICHOLLS, XIAO-PING DONG, GU JIANG, MALIK PEIRIS. Respirology 2003; 8 : S6-S8Severe acute respiratory syndrome (SARS) is caused by a novel coronavirus, called the SARS coronavirus (SARS-CoV). Over 95% of well characterized cohorts of SARS have evidence of recent SARSCoV infection. The genome of SARS-CoV has been sequenced and it is not related to any of the previously known human or animal coronaviruses. It is probable that SARS-CoV was an animal virus that adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 20 publications
3
79
0
2
Order By: Relevance
“…Previously, the reported receptor for SARS-CoV, the angiotensin 1 converting enzyme 2 (hACE2) had only been localized to alveolar cells in the lung although recent evidence indicates that hACE2 is present throughout the human airway epithelium suggesting additional cellular targets of infections (Jia et al, 2005) SARS-CoV specific RNA has also been localized in pulmonary macrophages although whether viable virus was present was not determined (Lu et al, 2005). In another study based on six patients who died from SARS the most pronounced morphological features were giant cell formation (predominately macrophages) and pneumocyte hyperplasia suggesting that proinflammatory cytokines released by stimulated macrophages in the alveolus were a predominant cause of pathogenesis (Nicholls et al, 2003a;Nicholls et al, 2003b). Histological samples for determining SARSCoV infection of airways have been less rigorously studied as pathological analyses is usually performed on late stage fatal cases (Chow et al, 2004;.…”
Section: Clinical Evidence For Sars-cov Pathogenesismentioning
confidence: 99%
“…Previously, the reported receptor for SARS-CoV, the angiotensin 1 converting enzyme 2 (hACE2) had only been localized to alveolar cells in the lung although recent evidence indicates that hACE2 is present throughout the human airway epithelium suggesting additional cellular targets of infections (Jia et al, 2005) SARS-CoV specific RNA has also been localized in pulmonary macrophages although whether viable virus was present was not determined (Lu et al, 2005). In another study based on six patients who died from SARS the most pronounced morphological features were giant cell formation (predominately macrophages) and pneumocyte hyperplasia suggesting that proinflammatory cytokines released by stimulated macrophages in the alveolus were a predominant cause of pathogenesis (Nicholls et al, 2003a;Nicholls et al, 2003b). Histological samples for determining SARSCoV infection of airways have been less rigorously studied as pathological analyses is usually performed on late stage fatal cases (Chow et al, 2004;.…”
Section: Clinical Evidence For Sars-cov Pathogenesismentioning
confidence: 99%
“…Two phases have been identified during SARS-CoV infection in humans (41). ARDS develops within the first 10 days with DAD, edema, and hyaline membrane formation (39,40). After the acute phase, organizing DAD with increased fibrosis is observed (40).…”
Section: Vol 81 2007 Lethal Sars-cov Infection In Aged Mice 7417mentioning
confidence: 99%
“…ARDS develops within the first 10 days with DAD, edema, and hyaline membrane formation (39,40). After the acute phase, organizing DAD with increased fibrosis is observed (40). ARDS has been shown to be the major cause of death in cases of human infection by SARS-CoV and avian influenza A (H5N1) (39) and likely the 1918 influenza virus (25).…”
Section: Vol 81 2007 Lethal Sars-cov Infection In Aged Mice 7417mentioning
confidence: 99%
“…[60,61]. No specific pathological patterns have been identified that is characteristic of SARS and appearances might be complicated with superimposed infections and immunomodulatory treatment modalities [62]. anaemia) and high-dose potent corticosteroids (hyperglycaemia, nosocomial infections and hypokalaemia).…”
Section: (B) Early Outcomes Of Sarsmentioning
confidence: 99%